Non-Isothermal sloshing for space applications: from a ground-based experimental characterisation to microgravity conditions - Monteiro, F (2022)
Liquid cryogenic propellants are at the forefront of space propulsion due to their optimal trade-off between performance and weight (Sutton et al. 2017). As a result, investigations on the sloshing dynamics of such fuels have been carried out since the early 1960s. Sloshing, defined as the movement of the free liquid surface within a reservoir (Abramson, 1966), induces two types of undesirable effects: (a) displacement of fuel tank’s centre of mass, which disturbs the stability and manoeuvrability of the spacecraft; (b) thermal mixing between the pressurised ullage and subcooled liquid, which can generate large fluctuations in the tank pressure, leading to structural instabilities and thrust oscillations in the propulsive system. [...]